The multifarious role of callose and callose synthase in plant development and environment interactions - Li, Ning; Lin, Zeng; Yu, Peiyao; Zeng, Yanling; Du, Shenxiu; Huang, Li-Jun (Frontiers in Plant Science, 2023)
Callose is an important linear form of polysaccharide synthesized in plant cell walls. It is mainly composed of β-1,3-linked glucose residues with rare amount of β-1,6-linked branches. Callose can be detected in almost all plant tissues and are widely involved in various stages of plant growth and development. Callose is accumulated on plant cell plates, microspores, sieve plates, and plasmodesmata in cell walls and is inducible upon heavy metal treatment, pathogen invasion, and mechanical wounding. Callose in plant cells is synthesized by callose synthases located on the cell membrane. The chemical composition of callose and the components of callose synthases were once controversial until the application of molecular biology and genetics in the model plant Arabidopsis thaliana that led to the cloning of genes encoding synthases responsible for callose biosynthesis. This minireview summarizes the research progress of plant callose and its synthetizing enzymes in recent years to illustrate the important and versatile role of callose in plant life activities.